Self-ordered pointing as a test of working memory in typically developing children - Cragg, Lucy; Nation, Kate (Psychology Press, 2007)
The self-ordered pointing test (SOPT; Petrides & Milner, 1982) is a test of non-spatial executive working memory requiring the ability to generate and monitor a sequence of responses. Although used with developmental clinical populations there are few normative data against which to compare atypical performance. Typically developing children (5!11 years) and young adults performed two versions of the SOPT, one using pictures of familiar objects and the other hard-to-verbalise abstract designs. Performance improved with age but the children did not reach adult levels of performance. Participants of all ages found the object condition easier than the abstract condition, suggesting that verbal processes are utilised by the SOPT. However, performance on the task was largely independent from verbal and nonverbal cognitive ability. Overall the results suggest that the SOPT is a sensitive measure of executive working memory.